(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Domestic violence against women remains a widespread global issue, significantly impeding gender equality, economic development, and the establishment of peaceful societies (SDGs 5, 8, & 16). This study explores the impact of financial inclusion strategies in mitigating domestic violence against women. Drawing on secondary evidence sourced from peer-reviewed literature, global databases, and institutional reports, grounded on an integrated theoretical framework combining Resource Theory with the Theory of Gender and Power. The study elucidates how financial inclusion may boost women's bargaining power, broaden their economic resources, and challenge established gender hierarchies. Findings show that financial inclusion significantly mitigates domestic violence when interventions are tailored to the specific context, promote gender equality, and are underpinned by strong institutional frameworks. The study makes recommendations for four principal stakeholders: policymakers should formulate gender-responsive financial inclusion policies; financial institutions are encouraged to create accessible and secure financial products tailored for women; civil society organizations are advised to implement community-based financial literacy and empowerment initiatives; and development partners are called upon to finance and oversee programs that blend economic empowerment with the prevention of gender-based violence. By doing so, strategic implementation of financial inclusion can serve as an effective mechanism to enhance women's safety and agency, thereby contributing to sustainable development and gender equality.